Strongly Enhanced Growth of High-Temperature Superconducting Films on an Advanced Metallic Template - Khan Mukarram Z; Rivasto Elmeri; Rijckaert Hannes; Zhao Yue; Liedke Maciej O; Butterling Maik; Wagner Andreas; Van Driessche Isabel; Huhtinen Hannu; Paturi Petriina (AMER CHEMICAL SOC, 2022)
We demonstrate a straightforward and easily applied technique for growing BaZrO3 doped YBa2Cu3O6+x films of highly improved quality on a commercially used buffered metallic template by pulsed laser deposition. Our method relies on reducing the grain size of the target material, which completely prevents the transfer of the harmful grain boundaries or weak links from the substrate through the buffer layers on the deposited film. We have also observed a great improvement in the self-assembly of BaZrO3 dopants, and the critical current density is increased in the high temperature range up to 40%. As an extra benefit, our method allows us to increasing the growth rate of the film by 25%. We have discussed the results comprehensively and provided quantitative insight into the underlying mechanisms. The presented technique can be considered a groundbreaking advancement for the vastly growing coated conductor industry.